Pricing and Production Decisions for New and Remanufactured Products - Feng Wei; Yan Zhu; Ting Ma; Qiaoyan Huang; Zengshan Zhen; Jinhui Chen (Complexity)
Remanufacturing widely exists in production activities. Two different game models are involved while considering reverse channels: (1) In Model P, the manufacturer provides new and remanufactured products to two retailers. New products are sold through an online platform (retailer R1), while remanufactured products are sold in offline physical stores (retailer R2) in a decentralized scenario. (2) In Model C, the manufacturer provides new and remanufactured units to only one retailer (retailer R) that operates both online and offline channels in a centralized scenario. This research showed that a manufacturer’s profitability and industry profits in Model P were higher than those in Model C from the perspective of economic performance; the sum of the profits of both retailers in Model P was worse than the profits of the retailer in Model C. Moreover, Model P was found to be greener than Model C from the perspective of environmental sustainability. From a social viewpoint, Model P had a higher consumer surplus than Model C; the higher the cost of distributing a remanufactured unit, the more disadvantageous the model to the consumers.